PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DITINJAU DARI KARAKTERISTIK PERUSAHAAN - Rachyu Purbowati; Rita Mutiarni (Universitas Medan Area, 2017)
Corporate social responsibility (CSR) is an action or concept undertaken by the company (according to the ability of the company) as a form of social or environmental responsibility where the company is located. This study aims to determine the effect of corporate characteristics on CSR disclosure either partially or simultaneously. This research includes explanatory research. The population used in this study is the company is listed on the Indonesia Stock Exchange in 2015. Samples taken in this study as many as 50 manufacturing companies listed on the BEI in 2015 that have been published. From the result of the research, it is known that partially Corporate Size Variable (X1) has significant influence to corporate social responsibility disclosure (CSR) (Y) level on Indonesian Stock Exchange company. While the Company Profile Variable (X2), Size Variable of Board of Commissioner (X3), Variable Concentration of Ownership (X4) have no significant influence to corporate social responsibility disclosure (YR) at Indonesian Stock Exchange. While simultaneous variable of Company Size (X1), Company Profile (X2), Size of Board of Commissioner (X3) and Concentration of Ownership (X4) have significant influence to corporate social responsibility disclosure (CSR) (Y). Variable Size Company (X1) has the most dominant influence on the disclosure of Corporate Social Responsibility (CSR) (Y).Keywords: Characteristics, Environment, Corporate Social Responsibility